Micronutrient status and fatty acid profile of adults with SARS-CoV-2 infection—an observational study - Bleffgen, Melanie; Schinhammer, Laura; De Rosa, Francesco Giuseppe; Scabini, Silvia; Brandl, Beate; Hauner, Hans; Bo, Simona; Skurk, Thomas (Frontiers in Nutrition, 2025)
IntroductionSARS-CoV-2 infection is a complex disease with multiple dimensions, involving factors that promote infection and virus-driven processes in many body organs. The micronutrient status, beyond others, acts as a potential confounder, influencing susceptibility to infection and disease severity. Additionally, the virus appears to alter lipid metabolism, which may serve a dual function, suppor viral replication while simultaneously contributing to the body’s defense and repair mechanisms.MethodsThis observational study compared micronutrient levels (vitamin D, selenium, zinc, magnesium, and iron) and lipid profiles between 139 SARS-CoV-2 -positive patients (62 hospitalized, 77 home care) and 314 healthy controls, using dried blood spots. We also examined differences by treatment setting (hospitalized vs. home care) as a proxy for disease severity.ResultsPatients with SARS-CoV-2 infection exhibited similar micronutrient levels but showed a significantly impaired lipid profile compared to healthy controls. Notably, there was a significant decrease in palmitic (p-value < 0.01) and stearic acid levels (p-value < 0.01) and a significant increase in omega-3 and omega-6 PUFAs, like AA (p-value < 0.01), DHA (p-value < 0.01), and EPA (p-value < 0.05) were detected. In the SARS-CoV-2 positive cohort, hospitalized patients had significantly lower micronutrient levels (p < 0.01 for all measured micronutrients) compared to those receiving home care.DiscussionThese findings suggest that SARS-CoV-2 infection alters lipid metabolism and that lower micronutrient status may be linked to greater disease severity.